Rapid fully-automated assay for routine molecular diagnosis of BRAF mutations for personalized therapy of low grade gliomas. (2nd January 2020) - Merlin, Marie-Sophie; Gilson, Pauline; Rouyer, Marie; Chastagner, Pascal; Doz, François; Varlet, Pascale; Leroux, Agnès; Gauchotte, Guillaume; Merlin, Jean-Louis
Abstract: Background: BRAF mutation analysis is important to personalize the management with low-grade gliomas (LGG) in children and adults, with therapeutic and prognostic impacts. In recurrent tumors, targeted therapies such as BRAF inhibitors had been reported to induce disease stabilization and significant radiographic responses. This highlights the potential interest of BRAF mutation to stratify patients for targeted therapy. Standard operating procedures (SOP) for BRAF V600E mutation detection can be time-consuming and consequently delay treatment choice in patients with acute deterioration. Here, we evaluated Idylla TM fully automated PCR (FA-PCR) assay for the rapid determination of BRAF mutational status in children and adult LGG. Methods: Formalin-fixed and paraffin-embedded (FFPE) samples from three histological LGG subtypes (ganglioglioma, pleomorphic xantoastrocytoma, and dysembryoplastic neuroepithelial tumor) with previous SOP-characterized BRAF mutational status were re-analyzed using the FA-PCR. Overall concordance with the mutational status determined using SOP, as well as sensitivity and specificity of FA-PCR technique were assessed. Results: All 14 samples gave interpretable results with FA-PCR. Overall concordance of BRAF mutational status between FA-PCR and SOP was 100%. Sensitivity and specificity were 100%. Conclusion: This study confirms the reliability of FA-PCR for BRAF mutations analysis in children and adult LGG. Considering the short time to results enabled by FA-PCR, providing results in less than 90 minutes, this technique represents an interesting option for the molecular diagnosis of LGG and personalization of treatment.